Predicting Chinese Adolescent Internet Gaming Addiction From Peer Context and Normative Beliefs About Aggression: A 2-Year Longitudinal Study - Su, Ping; Yu, Chengfu; Zhang, Wei; Liu, Sha; Xu, Yang; Zhen, Shuangju (Frontiers in Psychology, 2018)
There has been growing concern over Internet gaming addiction (IGA) around the world. However, about the Chinese participants, risk factors and mediating mechanisms of IGA remain largely unknown. A total of 323 Chinese adolescents(52.94% females, M age = 14.83, SD = 0.49, range = 13.50-16.50) completed questionnaires regarding peer victimization, deviant peer affiliation, normative beliefs about aggression, and IGA in the autumn of their 7th-9th grade years. Structural equation modeling showed that 7th grade peer victimization predicted higher 8th grade deviant peer affiliation, which in turn was associated with enhanced 9th grade normative beliefs about aggression, and ultimately, higher 9th grade IGA. In addition, 7th grade peer victimization made a unique contribution to 9th grade IGA through 9th grade normative beliefs about aggression. The current study goes beyond previous research by using a two-year longitudinal design and by taking into account both peer relations and individual cognition as predictors of IGA. In addition, these findings have practical significance for improving intervention strategies targeting risk factors for adolescent IGA.